First we solve what we can solve.
<span>y</span>-3= 2/3<span>(</span>x-1)
We first multiply
<span>y</span>-3= 2/3 (x) - 2/3
Then we move the -3 and it becomes +3 on the other side
y= 2/3 (x) - 2/3 + 3
And we solve what we can to get our answer.
y= 2/3 (x) + 2 1/3
Answer:
Add 2y and y.
Step-by-step explanation:
you have to combine what is common
plz give brainliest
Answer:
7(x)=5x+7
to find the x / zero intercept, plug in f (x) = 0
0=5x+7
move the left side and change the sign
-5x7
divide both of the equation by -5
x= 
same steps for g(x)=-2x-4
x=-2